Variations of the fundamental frequency in polish voiced consonants - MATUSZKINA, Olga (Archives of Acoustics, 2016)
The aim of work described in this paper was to verify and confirm the general thesis regarding the Polish language that the variations of the fundamental frequency in voiced consonants can sometimes agree with and some-times differ from the global tone line plotted on a tonogram for the sequence of the vowels. The evolutions of this line are considered to be critical in the perception of the intonation contour. Qualitative and quantitative descriptions of the character of variations of the fundamental tone in the voiced consonants /b/ /d/,g/,/7/,/v/ /z/, /3/, /y/, /m/, /n/, /n/, /r/ and /l/ are given. The relation between these changes and the type of articulation of the consonant was investigated. The results of the investigations support the assumption that such a relationship exists. In many respects this fact is in agreement with the data given in the relevant literature, and its explanation can be sought in the articulatory and physiological properties of the individual consonants.